Efektivitas Pemberian Reward Dalam Meningkatkan Kehadiran Santri Tpa di Masjid Al-Azhar - Sholihah, Annisa Nur; Dwi Ambarwati (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study was motivated by low student attendance at the Qur’anic Learning Center (TPA) of Al-Azhar Mosque, affecting religious learning activities. The aim was to analyze the effectiveness of rewards in improving attendance and motivation. The study used Participatory Action Research (PAR) with Participatory Rural Appraisal (PRA) techniques, involving interviews, observations, and documentation. The results showed that rewards such as praise, small gifts, and certificates successfully increased student attendance. Attendance rose from 60% to 85%, a 25% improvement after the program. Students’ motivation and participation in TPA activities also improved. Positive responses came from teachers and parents, noting that children were more enthusiastic and disciplined. However, challenges included some students remaining unaffected and the need for varied rewards to maintain interest. Overall, the reward program effectively increased student attendance and motivation and is recommended for continuous implementation with further innovation.